Downregulated microRNA-148b in circulating PBMCs in chronic myeloid leukemia patients with undetectable minimal residual disease: a possible biomarker to discontinue imatinib safely - Ohyashiki, Junko H (Dove Medical Press, 2014)
BACKGROUND: A subset of patients with chronic myeloid leukemia (CML) can sustain a complete molecular response after discontinuing imatinib mesylate (IM). We focused on microRNAs (miRNAs), with the aim of finding a molecular biomarker to discriminate which patients can safely and successfully discontinue IM use. METHODS: To identify miRNAs that showed altered expression in patients who had discontinued IM (STOP-IM group), we first screened miRNA expression of peripheral blood mononuclear cells by using a TaqMan miRNA array on samples from five unselected patients from the STOP-IM group, seven CML patients receiving IM (IM group), and five healthy volunteers. We then performed miRNA quantification in 49 CML patients with deep molecular response. Mann–Whitney U and chi-square tests were used to determine statistical significance for comparisons between the control (healthy volunteers) and test groups (STOP-IM and IM groups). Multiple groups were compared by one-way analysis of variance. RESULTS: Downregulation of miR-148b was noted in patients in the STOP-IM group and in a subset of the IM group. We then subdivided the IM patients into two groups: one with downregulated miR-148b expression (IM-1; less than the cut-off value) and the other without downregulated miR-148b expression (IM-2; greater than the cut-off value). The number of patients who had a sustained stable molecular response was significantly lower in IM-2 group. This group also had a significantly lower percentage of natural killer cells. CONCLUSION: Downregulated miR-148 may contribute to immune surveillance in STOP-IM patients and may therefore have potential as additive information in managing CML patients undergoing treatment with IM.